THU0289 Long Term Use of Hydroxychloroquine in Patients with Primary Antiphospholipid Syndrome: A Retrospective Cohort Study. (15th July 2016) - Nuri, E.; Taraborelli, M.; Andreoli, L.; Gerosa, M.; Argolini, L.M.; Meroni, P.L.; Tincani, A.
Abstract : Background: A potential role of hydroxychloroquine (HCQ) use in patients with antiphospholipid antibodies (aPL) has been suggested by some retrospective cohorts and in animal models based on its potential beneficial effects on autoantibody effect and titer, endothelial function and glucose or lipid metabolism [1–3]. Objectives: To evaluate the impact of HCQ on aPL titers, on glucose and cholesterol levels and its role in the prevention of thrombotic recurrences in Primary Antiphospholipid Syndrome (PAPS). Methods: Patients with PAPS, diagnosed according to 2006 Classification Criteria without any Connective Tissue Disease, that received HCQ (HCQ+) but no immunosuppressive drugs, were matched with similar patients that did not received HCQ (HCQ-) according to the following characteristics: same gender, follow-up duration, disease onset, age at the beginning of the follow-up ±10 years and initial date of the follow-up ± 5 years. Results: Seventy-two patients (36 HCQ+ and 36 HCQ-) with a mean follow-up of 77 (±SD 49) months between 1992 and 2015 were studied. No significant variations in demographical, clinical, serological features were observed between the two groups except for of anti-extractable nuclear antigen antibodies (19% in HCQ+ versus 0% in HCQ-, p:0.014). Anti-β2Glycoprotein I IgG titers were significantly lower in HCQ+ than in HCQ- patients at the end of the follow-up (Student t, p:0.018). The variations of all the aPL titers in the two groups are shown in Figure 1. No differences in glucose and cholesterol levels were detected. Eight percent of HCQ+ and 17% of HCQ- patients experienced a thrombosis during the follow-up. Among patients with a history of thrombosis the annual incidence of recurrences was lower (0, 87%) in HCQ+ patients than in HCQ- (2, 17%). Conclusions: This study showed a strong reduction of aPL titers and of the incidence of recurrences in patients treated with HCQ, supporting a possible role of this drug in the treatment of patients with PAPS. References: Rand JH, Wu XX, Quinn AS, et al. Hydroxychloroquine directly reduces the binding of antiphospholipid antibody-beta2-glycoprotein I complexes to phospholipid bilayers. Blood 2008, 112:1687–1695. Broder A, Putterman C. Hydroxychloroquine use is associated with lower odds of persisently positive antiphospholipid antibodies and/or lupus anticoagulant in systemic lupus erythematosus. J Rheumatol 2013, 40:30–33. Schmidt-Tanguy A, Voswinkel J, Henrion D, et al. Antithrombotic effects of hydroxychloroquine in primary antiphospholipid syndrome patients. Journal of Thrombosis and Haemostasis. 2013;11(10):1927–1929. Disclosure of Interest: None declared